The validity and reliability of a portable jumping measurement device (FITJUMP) for determining vertical jump performance in pre-adolescent children - Yildiz, M.; Fidan, U.; Birlik, S. (Measurement in Physical Education and Exercise Science, 2026)
This study aimed to evaluate the validity and reliability of the FITJUMP portable device for measuring vertical jump performance in pre-adolescent children. To assess concurrent validity, fifty participants performed three countermovement (CMJ) and squad jumps (SJ) simultaneously on a force platform (impulse-momentum calculation) and with the FITJUMP device. For test-retest reliability, participants repeated three CMJs and SJs using the FITJUMP device at 24-hour intervals. Very strong correlations were observed between the force platform and FITJUMP device measurements for CMJ and SJ (ICC = .89, and .92, respectively), with no systematic bias and minimal random error. Test-retest reliability was excellent, demonstrating high consistency for CMJ and SJ (ICC = .92, and .92, respectively) and very low coefficients of variation (CV = 6.1% and 4.9%, respectively). The Fitjump device was rated as "marginal at determining the SWC for CMJ (SWC: 0.51, TE: 1.80 and SJ (SWC: 0.47, TE: 1.16), respectively. These findings indicate that the FITJUMP portable device is a valid and reliable tool for assessing CMJ, and SJ height in pre-adolescent children. However, its sensitivity is questionable.